2023
DOI: 10.2147/jpr.s395421
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Acupuncture Therapy for Cancer Pain Over the Past 10 Years

Abstract: Cancer pain is a common symptom of cancer patients and greatly affects quality of life. Acupuncture has certain curative effects on cancer pain. The aim of this study was to analyze and visualize the current status and research trend of acupuncture treatment for cancer pain over the last 10 years and provide directions for future development. Methods: A search of the Web of Science Core Collection from 2012-01-01 to 2022-08-20 was performed to collect studies related to acupuncture therapy for cancer pain. Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 108 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…High-frequency and high-centrality keywords reflect the current research hotspots in a particular field [13] . We used CiteSpace to create a co-occurrence graph for the 110 keywords (Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
“…High-frequency and high-centrality keywords reflect the current research hotspots in a particular field [13] . We used CiteSpace to create a co-occurrence graph for the 110 keywords (Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the co-citation of journals provides a valuable means to visualize the distribution of information sources and identify noteworthy journals within a specific field. 24 In this study, a total of 2926 cited sources were referred by the 254 publications. Figure 2 portrays a comprehensive map comprising 51 journals that have been cited over 40 times each.…”
Section: Resultsmentioning
confidence: 99%
“… 23 Through this process, bibliometrics unveils current research hotspots and emerging trends in specific fields, providing valuable insights for academic decision-making. 24 CiteSpace and VOSviewer are prominent software tools for quantitative literature analysis. Previous publications have witnessed bibliometric investigations pertaining to the general status and research trends concerning acupuncture for CP.…”
Section: Introductionmentioning
confidence: 99%
“…The management of these symptoms with conventional drugs is generally unsatisfactory and subject to side effects, while acupuncture has been shown to relieve cancer-related pain safely [ 81 ]. In a bibliometric analysis summarizing research conducted between 2012 and 2022, acupuncture was suggested as a leading modality in the treatment of MM-related pain [ 82 , 83 ]. This is particularly in regard to treatment of chemotherapy-induced peripheral neuropathy (CIPN), which is an unmet need in Western medicine [ 80 ].…”
Section: Acupuncturementioning
confidence: 99%